2010
DOI: 10.1007/s11191-010-9276-5
|View full text |Cite
|
Sign up to set email alerts
|

Using History to Teach Mathematics: The Case of Logarithms

Abstract: Many authors have discussed the question why we should use the history of mathematics to mathematics education. For example, Fauvel (For Learn Math, 11(2): 3-6, 1991) mentions at least fifteen arguments for applying the history of mathematics in teaching and learning mathematics. Knowing how to introduce history into mathematics lessons is a more difficult step. We found, however, that only a limited number of articles contain instructions on how to use the material, as opposed to numerous general articles sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
(18 reference statements)
0
9
0
1
Order By: Relevance
“…It might be due to participants' inability to get the definition of logarithm and build connection to exponents. In this case, we made use of common conception that logarithm was the invers of raising to a power (exponents), thus we did not confirm the historical development of logarithm which emphasized the concept of geometric and arithmetic sequences (Fauvel, 1995;Katz, 1995;Panagiotou, 2011) as the basic theme when introducing logarithm. So, for instance, teachers should provide powerful explanation repetitively that c a b  can be expressed as log a b c  by using numerical example such as 3 2 2 8 log 8 3    .…”
Section: Graph Of Logarithm and Logarithmic Functionmentioning
confidence: 91%
“…It might be due to participants' inability to get the definition of logarithm and build connection to exponents. In this case, we made use of common conception that logarithm was the invers of raising to a power (exponents), thus we did not confirm the historical development of logarithm which emphasized the concept of geometric and arithmetic sequences (Fauvel, 1995;Katz, 1995;Panagiotou, 2011) as the basic theme when introducing logarithm. So, for instance, teachers should provide powerful explanation repetitively that c a b  can be expressed as log a b c  by using numerical example such as 3 2 2 8 log 8 3    .…”
Section: Graph Of Logarithm and Logarithmic Functionmentioning
confidence: 91%
“…Early works of Archimedes and Euclid contributed to the development of the multiplicative world and arithmetic and geometric series. Chuquet argued that multiplication of two numbers might be simplified to the addition of their natural orders [3]. For instance, 2 • 4 = 8 corresponded to 1+2 = 3.…”
Section: Historical Overview Of Thementioning
confidence: 99%
“…This is the conceptualization of "logarithms" by Napier and Briggs in the early 17th century and the "logarithmic curves" of Newton, Huygens and Agnesi at the end of the same century. A historical review of the emergence of logarithms can be found in Panagiotou (2011) andFerrari (2008). We will refer to the common covariational reasoning of both functions as logarithmic-exponential covariational reasoning.…”
Section: Purpose Of Researchmentioning
confidence: 99%